The effect of gallic acid addition to tris-based extender on frozen bull semen - Şükrü GÜNGÖR; Muhammed Enes İNANÇ; Deniz YENİ; Fatih AVDATEK; Ruhi TÜRKMEN; Umut TAŞDEMİR (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
This study aimed to determine the probable protective eff ect of gallic acid (GA) on the spermatological parameters of frozen‐thawed bull semen. Ejaculates were collected from four Holstein bulls. The mixed ejaculate was divided into four equal groups as control (0 μg/mL GA), 50, 100 and 200 μg/mL GA with a Tris-based extender. All extended groups were cooled, equilibrated into a +4°C cold cabinet and loaded into straws. The straws were then frozen and stored in a liquid nitrogen container (-196°C). Subsequently, samples were thawed in a water bath for analyzing motility and kinematic parameters, morphological integrity, DNA damage and biochemical alterations. GA50 (28.76±0.51%) and GA100 (29.32±0.31%) had improved progressive motility in comparison to the other groups (P<0.05). The highest total motility (69.71±0.52%) was detected in GA100 (P<0.05). Besides, the lowest DNA damage and total abnormality values were detected in the GA100 group (P<0.05). GA100 had the highest total antioxidant capacity, as well as the lowest malondialdehyde (MDA) level (P<0.05). In conclusion, GA 50 and 100 μg/mL protects the progressive motility, morphological and DNA integrity by improving the total antioxidant status from the harmful eff ects of the freezing and thawing protocol.